A high-efficiency recycling method of waste crystalline silicon cell piece
Patent Information
- Application Number
- CN202610966902.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-01
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-01
AI Technical Summary
然而,仍存在诸多问题:一是常用的硝酸体系会产生大量的氮氧化物废气,环境污染严重,且对银栅线的溶解性强,导致宝贵的银资源以离子形式进入废液,回收成本高、纯度低;二是现有的刻蚀工艺往往难以精准控制各层(铝背场、银栅线、氮化硅减反射膜、氧化层)的去除顺序和深度,容易导致硅晶圆过度腐蚀,降低硅圆的完整性和回收率;三是工艺流程繁琐,往往需要多步酸碱交替处理,试剂消耗大,废水产生量高
[0027]1. 攻克了致密氮化硅层难刻蚀的技术瓶颈:通过“高浓度磷酸(>80%)+ 高温(>140℃)+ 氟化铵除垢”的三重协同作用,成功解决了致密氮化硅层导致的刻蚀停滞问题,实现了银栅线的高效、高纯(97%)固态回收。
Smart Images

Figure CN122500037B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a crystalline silicon recycling technology, specifically a method for recycling waste crystalline silicon solar cells. Background Technology
[0002] In the photovoltaic (PV) industry, crystalline silicon solar cells hold over 94% of the market share due to their high conversion efficiency, good stability, and relatively controllable cost. However, as early-installed PV power plants gradually reach the end of their service life (typically 25-30 years), and due to the defect rate during the production process, a large number of waste crystalline silicon solar cells are generated. These waste cells not only contain high-value silicon wafers but are also rich in metal resources such as silver and aluminum. Improper handling not only results in a huge waste of resources but also poses a serious environmental pollution risk to soil and water sources due to the heavy metals and chemicals they contain. Therefore, developing efficient and environmentally friendly waste crystalline silicon solar cell recycling technologies to achieve the high-value reuse of resources such as silicon and silver has significant economic and social value.
[0003] Currently, the main methods for recycling waste crystalline silicon solar cells include physical crushing and sorting, pyrometallurgical methods, and wet chemical etching. While physical crushing and sorting is simple to operate, it is difficult to completely separate the tightly adhered electrode paste (silver, aluminum) from the silicon wafer, and it easily causes secondary crushing of the silicon wafer, resulting in low-purity recycled silicon that can only be used as low-end metallurgical-grade silicon. Pyrometallurgical methods remove impurities through high-temperature melting, which, although processing large volumes, consumes extremely high amounts of energy and easily introduces new impurities during the high-temperature process, resulting in low silicon yield. Furthermore, precious metals such as silver are easily lost through volatilization or require complex subsequent refining steps.
[0004] Wet chemical etching is a widely researched method, typically using strong acid mixtures such as nitric acid and hydrofluoric acid to remove surface antireflective coatings and electrodes. However, several problems remain: First, the commonly used nitric acid system generates large amounts of nitrogen oxide waste gas, causing severe environmental pollution. Furthermore, its strong solubility for silver grid lines results in valuable silver resources entering the waste liquid in ionic form, leading to high recovery costs and low purity. Second, existing etching processes often struggle to precisely control the removal sequence and depth of each layer (aluminum back surface, silver grid lines, silicon nitride antireflective coating, oxide layer), easily leading to over-etching of the silicon wafer, reducing its integrity and recovery rate. Third, the process is cumbersome, often requiring multiple acid-base alternating treatments, resulting in high reagent consumption and wastewater generation. Moreover, existing methods, after removing the surface silicon nitride and oxide layers, often fail to directly obtain silicon wafers with a purity of 2N (99%) or higher, and the overall recovery rate of silicon material is generally below 90%, failing to meet the demand for high-quality recycled silicon.
[0005] Therefore, designing a method for recycling waste crystalline silicon solar cells that can selectively dissolve the aluminum back surface field, recover high-purity silver grid lines in solid form, and precisely remove silicon nitride and oxide layers is a technical challenge that urgently needs to be solved in the current photovoltaic recycling field. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide an efficient recycling method for waste crystalline silicon solar cells. Through a stepwise chemical etching strategy, the method achieves efficient separation of silver and aluminum grid lines from silicon wafers and precise removal of silicon nitride and oxide layers, with a total silicon material recovery rate of over 96%.
[0007] The technical solution adopted by this invention to solve its technical problem is a highly efficient recycling method for waste crystalline silicon solar cells, comprising the following steps:
[0008] S1. Waste crystalline silicon solar cells are placed in a mixed solution of phosphoric acid and ammonium fluoride to react, dissolving the aluminum back surface and initially etching the silicon nitride layer, causing the silver grid lines to detach. Solid-liquid separation yields regenerated silver grid lines and filter cake; wherein, the mass fraction of phosphoric acid in the mixed solution is ≥80%;
[0009] S2. Continue to soak the filter cake in the mixed solution of step S1 to completely etch the silicon nitride layer and obtain a silicon wafer;
[0010] S3. The silicon wafer is immersed in sodium hydroxide solution to remove the oxide layer on the surface, and then cleaned and dried to obtain a high-purity silicon wafer.
[0011] In step S1, there is a significant difference in the density of silicon nitride (SiNx) on the front and back sides of the crystalline silicon solar cell: the silicon nitride layer on the front side, which serves as an anti-reflective coating, has an extremely dense structure, while the silicon nitride in the aluminum back field region on the back side is relatively porous. When the phosphoric acid mass fraction is below 80%, the acid solution's oxidizing and penetrating abilities are insufficient, only able to dissolve the aluminum grid lines, and unable to effectively destroy the dense silicon nitride lattice structure on the front side. The silver grid lines covering it will not be able to fully contact the acid solution or be completely peeled off from the silicon substrate, resulting in failed silver recovery or extremely low purity. During the phosphoric acid etching of silicon nitride, silicon dioxide (SiO2) byproducts are generated. Due to the density of the silicon nitride layer on the front side, the generated SiO2 easily adheres to the surface to form a passivation layer, hindering the phosphoric acid from continuing to react with the inner silicon nitride layer, leading to etching stagnation. The addition of ammonium fluoride (NH4F) is a key technical feature. It can quickly dissolve the SiO2 generated in the reaction (to generate soluble ammonium fluorosilicate), eliminate the passivation layer barrier, and allow phosphoric acid to continue to react deeply, thereby ensuring that the dense silicon nitride layer is completely removed and the silver gate line is fully released.
[0012] Because a non-oxidizing acid system (mainly phosphoric acid) was used, the silver did not undergo oxidation and dissolution, and was thus directly recovered in the form of high-purity elemental metal.
[0013] Furthermore, in step S1, the separated regenerated silver grid lines are cleaned and dried, and their purity reaches over 97%.
[0014] Further, in step S1, the mass fraction of phosphoric acid in the mixed solution is 80%-85%, and the amount of ammonium fluoride added is 0.05%-0.10% of the mass of phosphoric acid. In this invention, there is no limitation on the ratio of waste crystalline silicon solar cells to the mixed solution; the mixed solution is sufficient to completely submerge the waste crystalline silicon solar cells.
[0015] When the temperature is below 140℃, phosphoric acid can only dissolve aluminum and cannot etch silicon nitride, thus preventing the recovery of silver.
[0016] Furthermore, in step S1, the reaction temperature is 140℃-165℃, and the reaction time is 5 min-15 min.
[0017] Step S2 aims to thoroughly remove the residual silicon nitride antireflective coating on the front side by utilizing the activity of the remaining acid solution. At this point, the main residue on the silicon wafer surface is the natural oxide layer, and the purity has been increased to 98%.
[0018] Furthermore, in step S2, the etching temperature is 140℃-165℃.
[0019] When the temperature is below 140℃, phosphoric acid can only dissolve aluminum and cannot etch silicon nitride, thus preventing the recovery of silver.
[0020] Step S3 is the alkaline washing process to remove silicon oxide, thereby obtaining silicon wafers with a purity of 2N and a total silicon recovery rate of 96% or higher. This process involves a strict balance window between "over-etching" and "under-etching".
[0021] When the mass fraction of sodium hydroxide solution exceeds 20%, the corrosiveness of the alkaline solution on silicon wafers increases dramatically. It not only removes the oxide layer but also etches a large amount of silicon material, resulting in severe thinning of the silicon wafer or even perforation, which greatly increases the loss rate of silicon material.
[0022] When the mass fraction of the solution is less than 5% at room temperature and the processing time is less than 40 minutes, the alkaline solution cannot completely remove the stubborn silicon oxide layer and trace residual impurities on the silicon wafer surface, resulting in insufficient etching and the purity cannot reach the 2N level.
[0023] When the processing temperature exceeds 40°C and the time exceeds 10 minutes, the reaction rate is too fast, resulting in over-etching of the silicon wafer.
[0024] Furthermore, in step S2, the etching time is 8 min-15 min.
[0025] Furthermore, in step S3, the mass fraction of the sodium hydroxide solution is 5%-20%, the soaking temperature is room temperature to 40°C, and the soaking time is 10 min-60 min.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. Overcame the technical bottleneck of difficult etching of dense silicon nitride layers: Through the triple synergistic effect of "high concentration phosphoric acid (>80%) + high temperature (>140℃) + ammonium fluoride descaling", the etching stagnation problem caused by dense silicon nitride layers was successfully solved, and efficient and high-purity (97%) solid-state recovery of silver grid lines was achieved.
[0028] 2. Achieved ultimate optimization of silicon recovery rate: By precisely defining the critical parameters of sodium hydroxide etching, it avoids both insufficient etching (low purity) caused by low concentration / short time and over-etching (high loss) caused by high concentration / high temperature / long time, and stabilizes the total silicon material recovery rate at over 96%.
[0029] 3. Short and green process: No complex physical crushing or high-temperature smelting is required. Chemical selective etching can simultaneously achieve four objectives: aluminum removal, silver extraction, film removal, and polishing. The reagent cost is low and there are no toxic gas emissions, making it highly valuable for industrial application.
[0030] 4. Excellent product quality: The obtained recycled silicon wafers maintain good crystal structure and surface flatness, and impurities are thoroughly removed. They can be directly used to prepare solar-grade polycrystalline silicon or as high-quality metallurgical-grade silicon raw materials, which significantly improves the economic added value of waste photovoltaic modules. Attached Figure Description
[0031] Figure 1 These are photographs of waste crystalline silicon solar cells and recycled silver from Embodiment 1 of the present invention;
[0032] in, Figure 1 (a) is a photograph of discarded crystalline silicon solar cells; Figure 1 (b) is a partial SEM image of the Ag grid lines in a waste crystalline silicon solar cell; Figure 1 (c) is a photograph of the regenerated Ag grid line.
[0033] Figure 2 The images show SEM images of silver before and after treatment with phosphoric acid and ammonium fluoride in Example 2 of this invention.
[0034] in, Figure 2 (a) Morphology of the silver electrode on the waste crystalline silicon solar cell before treatment with phosphoric acid and ammonium fluoride; Figure 2 (b) shows the morphology of regenerated silver after treatment with phosphoric acid and ammonium fluoride.
[0035] Figure 3This is a SEM image of the high-purity silicon wafer obtained in Example 2 of the present invention.
[0036] Figure 4 The images shown are the SEM and EDS spectra of the silicon wafer product obtained in Comparative Example 5 of this invention.
[0037] in, Figure 4 (a) is a SEM image; Figure 4 (b) is the EDS energy spectrum.
[0038] Figure 5 These are photographs of silicon wafer products obtained after processing in the embodiments and comparative examples of the present invention;
[0039] in, Figure 5 (a) A photograph of the high-purity silicon wafer obtained in Example 1; Figure 5 (b) A photograph of the high-purity silicon wafer obtained in Example 2; Figure 5 (c) is a photograph of the silicon wafer product obtained in Comparative Example 1; Figure 5 (d) is a photograph of the silicon wafer product obtained in Comparative Example 2; Figure 5 (e) is a photograph of the silicon wafer product obtained in Comparative Example 3; Figure 5 (f) is a photograph of the silicon wafer product obtained in Comparative Example 4; Figure 5 (g) is a photograph of the silicon wafer product obtained in Comparative Example 5; Figure 5 (h) is a photograph of the silicon wafer product obtained in Comparative Example 6. Detailed Implementation
[0040] Many specific details of the invention are set forth in the following description to enable those skilled in the art to implement and fully understand the invention. However, the invention can be practiced in many other ways different from those described herein, and those skilled in the art can make various modifications without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art.
[0042] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Unless otherwise specified, the reagents and other materials used in this embodiment are all commercially available products.
[0043] The XRF elemental analysis results of the waste crystalline silicon solar cells used in the examples and comparative examples are shown in Table 1.
[0044] Table 1. Elemental composition of waste crystalline silicon solar cells
[0045]
[0046] Example 1
[0047] This embodiment provides an efficient recycling method for waste crystalline silicon solar cells, comprising the following steps:
[0048] S1. Take 26 g of waste crystalline silicon solar cells and place them in a polytetrafluoroethylene (PTFE) reactor. Add 250 mL of 85% phosphoric acid solution and 0.05% ammonium fluoride (NH4F) by mass of phosphoric acid, immersing the waste crystalline silicon solar cells in the phosphoric acid-ammonium fluoride mixed solution. Heat the reaction system to 165°C and maintain the temperature for 8 min. Under these conditions, preliminary etching is performed. The aluminum back field is completely dissolved, and the dense silicon nitride layer on the front side is effectively etched and peeled off with the assistance of ammonium fluoride, while the silver grid lines remain solid and intact. Filter while hot to separate the solid material, which mainly consists of silver grid lines and filter cake. After washing and drying with deionized water, the silver grid lines are recycled silver (grid lines).
[0049] S2. The filter cake obtained from step S1 is returned to the reactor. Using the remaining phosphate-ammonium fluoride mixed solution (or a small amount of phosphate-ammonium fluoride mixed solution of the same concentration as in step S1), the mixture is immersed and etched at 165°C for 12 min to thoroughly remove the residual silicon nitride antireflection film.
[0050] S3. Take out the silicon wafer obtained in step S2, rinse it with deionized water until neutral, and then immerse it in a 10% sodium hydroxide (NaOH) solution. Immerse it at room temperature (approximately 25°C) for 45 minutes to remove the natural oxide layer and trace impurities on the surface. Finally, clean it with ultrasound and dry it to obtain 25.09 g of high-purity silicon wafer. The obtained high-purity silicon wafer is as follows: Figure 5 As shown in (a), the surface is smooth and there is no obvious etching.
[0051] Figure 1 (a) is a photograph of discarded crystalline silicon solar cells; Figure 1 (b) is a partial SEM image of the Ag grid lines in a waste crystalline silicon solar cell; Figure 1 (c) is a photograph of the regenerated Ag grid line, showing that the silver grid line is separated in solid form in this embodiment.
[0052] Example 2
[0053] This embodiment provides an efficient recycling method for waste crystalline silicon solar cells, comprising the following steps:
[0054] S1. Take 19.24 g of waste crystalline silicon solar cells and place them in a polytetrafluoroethylene (PTFE) reactor. Add 250 mL of 80% phosphoric acid solution and 0.1% ammonium fluoride (NH4F) by mass of phosphoric acid, immersing the waste crystalline silicon solar cells in the mixed solution. Heat the reaction system to 140°C and maintain the temperature for 15 min. Under these conditions, preliminary etching is performed. The aluminum back surface is completely dissolved, and the dense silicon nitride layer on the front side is effectively etched and peeled off with the assistance of ammonium fluoride, while the silver grid lines remain solid and intact. Filter while hot to separate the solid material. This solid is mainly silver grid lines. After washing with deionized water and drying, regenerated silver grid lines are obtained.
[0055] S2. Return the filter cake filtered in S1 to the reactor, and continue to immerse and etch at 140°C for 15 minutes using the remaining acid solution or by adding a small amount of acid solution of the same concentration. Deep etching is used to completely remove the residual silicon nitride antireflection film layer.
[0056] S3. Take out the silicon wafer obtained in S2, rinse it with deionized water until neutral, and then immerse it in a 5% sodium hydroxide (NaOH) solution. Soak it at 40°C for 60 min to remove the natural oxide layer and trace impurities on the surface. Finally, it is ultrasonically cleaned and dried to obtain 18.41 g of high-purity silicon wafer.
[0057] Depend on Figure 2 (a) and Figure 2 (b) It can be seen that no obvious etching was observed on the surface of the silver gate lines after step S1, and the surface morphology of the silver gate lines was not significantly affected. The surface silver gate lines can be separated relatively completely after step S1. The obtained high-purity silicon wafer was analyzed by SEM, and the results are as follows: Figure 3 As shown, the surface silicon nitride has been largely removed, and the silicon wafer surface is smooth with no obvious etching marks. The resulting high-purity silicon wafer is shown in the image. Figure 5 As shown in (b), the surface is smooth and there is no obvious etching.
[0058] Comparative Example 1
[0059] The difference between this comparative example and Example 1 is that in step S1, 20 g of waste crystalline silicon solar cells were mixed with a 70% phosphoric acid solution. This resulted in 18.54 g of silicon wafer product.
[0060] Comparative Example 2
[0061] The difference between this comparative example and Example 1 is that in step S1, 26 g of waste crystalline silicon solar cells were used, and the reaction system was heated to 120°C. This ultimately yielded 24.42 g of silicon wafer product.
[0062] Comparative Example 3
[0063] The difference between this comparative example and Example 1 is that: 18.6 g of waste crystalline silicon solar cells were used, and in step S3, the mass fraction of sodium hydroxide solution was 25%. The final yield was 16.42 g of silicon wafer product.
[0064] Comparative Example 4
[0065] The difference between this comparative example and Example 1 is that 22 g of waste crystalline silicon solar cells were heated to 65°C in step S3. This resulted in 17.73 g of silicon wafer product.
[0066] Comparative Example 5
[0067] The difference between this comparative example and Example 1 is that in step S1, 24 g of waste crystalline silicon solar cells were used without the addition of ammonium fluoride. The final yield was 14 g of silicon wafer product.
[0068] The obtained silicon wafer products were analyzed by SEM, and the results are as follows: Figure 4 As shown in (a), there are still traces of incomplete etching on the surface; EDS analysis shows that... Figure 4 As shown in (b), there is residual silicon nitride on the surface.
[0069] Comparative Example 6
[0070] The difference between this comparative example and Example 1 is that in step S1, 30.7 g of waste crystalline silicon solar cells were mixed with 5% aminosulfonic acid in a phosphoric acid solution. This resulted in 27.50 g of silicon wafer product.
[0071] The recovery rates of the (high-purity) silicon wafer products obtained in the examples and comparative examples were obtained by weighing. The recovery rate and purity of the recycled silver were determined by ICP-OES, and the purity of the silicon wafers was determined by ICP-MS. The recovery rates and purity of the silicon wafer products obtained in the examples and comparative examples are shown in Table 2.
[0072] The recovery rate of Ag from the battery was assessed by its leaching rate in an acidic solution. The leaching rate was calculated using the following formula (1):
[0073] Ex= ×100%(1)
[0074] In the formula: Ex is the leaching efficiency of Ag (%); c1 is the content of Ag in the cell (mg / g); m is the mass of the cell before leaching (g); c2 is the content of Ag in the leachate after leaching (mg / ml); V is the volume of the leachate (ml).
[0075] Table 2
[0076]
[0077] Table 2 shows that Comparative Example 1 had a low phosphoric acid concentration, and Comparative Example 2 had an insufficient reaction temperature. The reaction system could not overcome the reaction barrier of the dense silicon nitride layer on the front side, leaving a large amount of silicon nitride residue on the silicon wafer surface. Because the silicon nitride layer was not completely removed, some of the silver gate lines covering it failed to detach, resulting in the recovered silver containing silicon and silicon nitride fragments, with a purity of only about 92%. Ultimately, the purity of the silicon wafer product was only 94.6%, failing to reach the 2N level. Figure 5 (c) and Figure 5 (d) also shows obvious silicon nitride residue.
[0078] As shown in Table 2, the Si recovery rate in Comparative Examples 3 and 4 was significantly reduced. Figure 5 (e) and Figure 5 (f) It can be seen that the silicon wafer products obtained in Comparative Examples 3 and 4 showed obvious roughening and a large number of corrosion pits on the surface, and some thin silicon wafers even showed perforation. This is because under the action of high concentration of alkaline solution or high temperature, the etching process not only removed the oxide layer, but also severely corroded the silicon wafer itself (over-etching).
[0079] After approximately 3 minutes of reaction in Example 5, the rate significantly slowed down until it stopped. Analysis revealed that the generated silica (SiO2) adhered to the dense silicon nitride surface, forming a passivation layer that hindered further penetration of phosphoric acid. Ultimately, the silicon nitride removal rate was only 60%, and the silver grid wire recovery was incomplete. Figure 5 (g) It can be seen that a large number of impurities remain on the surface of the silicon wafer. This fully demonstrates the key role of ammonium fluoride in dissolving the byproduct SiO2 and maintaining the continuous progress of the reaction.
[0080] Comparative Example 6 added aminosulfonic acid to the existing examples. The introduction of aminosulfonic acid into the phosphate-ammonium fluoride-based etching system significantly increased the overall acidity of the system, promoting the combination of fluoride ions and hydrogen ions in the solution to generate more active etching component HF, thus increasing the instantaneous effective etching concentration. Figure 5 (h) It can be seen that, compared with the single phosphate-ammonium fluoride system (Example 1), the composite system significantly accelerates the etching reaction rate of the silicon wafer surface and the back of the silicon substrate, and the etching effect is more concentrated and more intense, ultimately causing spot-like uneven etching defects on the back of the silicon wafer, resulting in a decrease in silicon recovery rate.
[0081] The above description is merely a preferred embodiment of the present invention, and the scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A method for the efficient recycling of waste crystalline silicon solar cells, characterized in that, Includes the following steps: S1. Waste crystalline silicon solar cells are placed in a mixed solution of phosphoric acid and ammonium fluoride and reacted at a temperature of 140℃-165℃ for 5 min-15 min. This process dissolves the aluminum back surface and preliminarily etches the silicon nitride layer, causing the silver grid lines to detach. Solid-liquid separation yields regenerated silver grid lines and a filter cake. The mixed solution contains 80%-85% phosphoric acid by mass, and the amount of ammonium fluoride added is 0.05%-0.10% of the phosphoric acid by mass. S2. Continue to immerse the filter cake in the mixed solution of step S1 to completely etch the silicon nitride layer and obtain a silicon wafer; the etching temperature is 140℃-165℃ and the etching time is 8 min-15 min. S3. The silicon wafer is immersed in sodium hydroxide solution to remove the oxide layer on the surface, and then cleaned and dried to obtain a high-purity silicon wafer. The mass fraction of the sodium hydroxide solution is 5%-20%. The immersion temperature is room temperature to 40°C. In step S3, the immersion time is 10 min-60 min.
2. The efficient recycling method for waste crystalline silicon solar cells according to claim 1, characterized in that, In step S1, the separated regenerated silver grid lines are cleaned and dried, and their purity reaches over 97%.
Citation Information
Patent Citations
Method for cleaning small square sheets of waste silicon materials
CN102151668A
Recovery method for waste silicon solar cells
CN108339832A
Method for extracting monocrystalline silicon from solar photovoltaic panel by using single reagent
CN118637626A
Method for efficiently recovering waste solar crystalline silicon battery component
CN121320734A